2017
DOI: 10.1515/johh-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Pre-event water contributions and streamwater residence times in different land use settings of the transboundary mesoscale Lužická Nisa catchment

Abstract: Abstract:The objective of the study was to evaluate the spatial distribution of peakflow pre-event water contributions and streamwater residence times with emphasis on land use patterns in 38 subcatchments within the 687 km 2 large mesoscale transboundary catchment Lužická Nisa. Mean residence times between 8 and 27 months and portions of preevent water between 10 and 97% on a storm event peakflow were determined, using 18 O data in precipitation and streamwater from a weekly monitoring of nearly two years. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Shanley et al [2] noted that event water contribution correlated positively with catchment size and open land cover. Šanda et al [3] addressed the influence of land use on pre-event water contribution. They found that the pre-event water contribution decreased with increasing forest cover, particularly due to the retention of water via interception and transpiration losses of soil water.…”
Section: Introductionmentioning
confidence: 99%
“…Shanley et al [2] noted that event water contribution correlated positively with catchment size and open land cover. Šanda et al [3] addressed the influence of land use on pre-event water contribution. They found that the pre-event water contribution decreased with increasing forest cover, particularly due to the retention of water via interception and transpiration losses of soil water.…”
Section: Introductionmentioning
confidence: 99%
“…Less abundant cation is the sum of Na + and K + and the less abundant anion is SO 4 2-. Mg 2+ and the sum of NO 3 -and Cl -are present only marginally. This is a typical pristine water type originating in carbonate rocks, with potential of drinking water use.…”
Section: Fig 3: Photo Of the Ploučnice Spring (June 22 Nd 2016)mentioning
confidence: 88%
“…The abundant surface water and groundwater resources in the region Liberec-Zittau and its surroundings have been recently addressed by several transboundary projects [1], [2], [3]. These studies have dominantly addressed the groundwater and surface water hydrology and/or their links to the land use and human activities.…”
Section: Introductionmentioning
confidence: 99%
“…Several years of data are recommended to justify the MTT (Herrmann & Stichler, ). However, the presented formula has been called the “sine curve approach” and applied in shorter term studies (e.g., Reddy, Schuster, Kendall, & Reddy, ; Šanda et al, ; Soulsby, Malcolm, Ferrier, Helliwell, & Jenkins, ). Here, we used one hydrological year of data to get a first approximation of the MTT in our catchments.…”
Section: Methodsmentioning
confidence: 99%